A kind of high water retention rate gypsum self-leveling mortar and preparation method thereof

By using composite water retention agents and other regulators in gypsum self-leveling mortar, the problem that mortar is difficult to retain moisture for a long time is solved, and its water retention rate and crack resistance are significantly improved, and construction quality and service life are improved.

CN119751008APending Publication Date: 2025-04-04KUNSHAN BAIYI NEW BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411843677.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-14
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In actual application, it is difficult to retain moisture for a long time, resulting in the mortar being prone to cracking in a dry environment, affecting the construction quality and service life.

Method used

Compound water retention agents, including hydroxypropyl methylcellulose and polyacrylate, are used to improve the water retention rate of the mortar by forming a three-dimensional network structure and electrostatic attraction; at the same time, polycarboxylic acid water reducing agent, retarder and modified wollastonite powder are used to regulate the fluidity and crack resistance of the mortar; reinforcement fibers further enhance the stability of the three-dimensional network structure and enhance crack resistance.

Benefits of technology

It significantly improves the water retention rate and crack resistance of gypsum self-leveling mortar, improves the fluidity and construction quality of the mortar, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005188555760000091
    Figure BDA0005188555760000091
  • Figure BDA0005188555760000101
    Figure BDA0005188555760000101
Patent Text Reader

Abstract

The present application relates to a high water retention gypsum self-leveling mortar and a preparation method thereof, and relates to the field of building materials, which includes the following components by mass: 60-80 parts of semi-hydrated gypsum, 4-8 parts of composite water-retaining agent, 0.1-0.5 parts of polycarboxylic acid water-reducing agent, 5-15 parts of wollastonite powder, 0.008-0.012 parts of retarder, 1-3 parts of reinforcing fiber and 15-25 parts of water; the composite water-retaining agent includes hydroxypropyl methylcellulose and polyacrylate. The preparation method includes the following steps: dispersing the composite water-retaining agent into water, stirring to obtain a water-retaining agent solution; adding the polycarboxylic acid water-reducing agent and the retarder to the water-retaining agent solution, stirring to obtain a mixed solution; adding wollastonite powder and semi-hydrated gypsum to the mixed solution, stirring to obtain a slurry; adding reinforcing fiber to the slurry, stirring to obtain a high water retention gypsum self-leveling mortar. The present application has the effect of improving the water retention rate of gypsum self-leveling mortar, and the mortar has good fluidity and anti-cracking performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of building materials, and in particular to a high water retention gypsum self-leveling mortar and a preparation method thereof. Background Art

[0002] Gypsum self-leveling mortar is a material widely used in construction, mainly used for ground leveling and improving ground flatness. In recent years, with the rapid development of the construction industry, the demand for self-leveling mortar has continued to increase. High water retention gypsum self-leveling mortar has been widely used in building decoration and renovation projects due to its excellent fluidity and strength after hardening. This material can not only improve construction efficiency, but also effectively reduce labor costs and improve the overall quality of the building. However, the existing gypsum self-leveling mortar still has some shortcomings in practical applications, and further improvements are needed to meet higher construction requirements.

[0003] At present, in order to improve the performance of gypsum self-leveling mortar, the following technical means are usually adopted: first, by adding different types of additives to improve the fluidity, water retention, crack resistance and strength of the mortar; second, optimize the selection of raw materials, such as using different types of gypsum powder and other additives; third, adjust the proportion of each component to achieve the best comprehensive performance. Common additives include water retaining agents, retarders, water reducing agents and fillers, etc. These additives can improve the performance indicators of mortar to a certain extent.

[0004] Although the above methods have improved the performance of gypsum self-leveling mortar to a certain extent, there are still some defects in practical application. Especially in terms of water retention, the existing gypsum self-leveling mortar is often difficult to retain moisture for a long time, which causes the mortar to crack easily in a dry environment, affecting the construction quality and service life. Therefore, how to improve the water retention rate of gypsum self-leveling mortar has become a key issue that needs to be solved urgently. Summary of the invention

[0005] In order to improve the water retention rate of gypsum self-leveling mortar, the present application provides a gypsum self-leveling mortar with high water retention rate and a preparation method thereof.

[0006] The present application provides a high water retention gypsum self-leveling mortar and a preparation method thereof using the following technical solutions: In the first aspect, the present application provides a high water retention gypsum self-leveling mortar, which adopts the following technical solution: A high water retention gypsum self-leveling mortar comprises the following components in parts by weight: 60-80 parts of hemihydrate gypsum 4-8 parts of composite water retaining agent Polycarboxylate water reducer 0.1-0.5 parts Wollastonite powder 5-15 parts Retarder 0.008-0.012 parts Reinforced fiber 1-3 parts 15-25 parts water; The composite water-retaining agent comprises hydroxypropyl methylcellulose and polyacrylate.

[0007] Hydroxypropyl methylcellulose in the composite water retaining agent forms hydrogen bonds with water molecules through the hydroxyl groups on the molecular chain, and entangles with each other to form a three-dimensional network structure. Polyacrylic acid salt relies on a large number of hydrophilic groups such as carboxyl groups to absorb water molecules through electrostatic attraction and hydrogen bonds. The two are interwoven to form a stable water retention system, thereby greatly improving the water retention rate and improving the rheological properties; the three-dimensional network structure can appropriately increase the viscosity, make the mortar flow smoothly, and evenly distribute the particles to prevent segregation. Polyacrylic acid salt is adsorbed on the surface of gypsum particles to generate electrostatic repulsion, reducing the friction between particles. The combination of the two allows the mortar to flow more smoothly while maintaining a certain viscosity; polycarboxylic acid water reducer and retarder work synergistically with the composite water retaining agent to regulate the performance of the mortar, improve its water retention rate, fluidity and crack resistance; wollastonite powder can fill pores and reduce water loss channels, thereby improving water retention performance; reinforcing fibers can improve the stability of the three-dimensional network structure and reinforce defects, thereby improving crack resistance.

[0008] Preferably, the hydroxypropyl methylcellulose is subjected to modification treatment to obtain a modified cellulose ether water-retaining agent, and the raw materials for preparing the modified cellulose ether water-retaining agent include hydroxypropyl methylcellulose body, maleic anhydride and chlorosulfonic acid.

[0009] Maleic anhydride can introduce more polar groups into the molecular chain of cellulose ether and enhance its adsorption capacity for water molecules; chlorosulfonic acid can further change its molecular structure, introduce sulfonic acid groups, increase its hydrophilicity and the number of sites for binding with water molecules, so that the modified cellulose ether water retaining agent can lock moisture in the mortar more effectively and further improve the water retention rate; its optimized molecular structure can better adjust the rheological properties of the mortar, improve the interaction between particles and enhance fluidity; stronger water retention capacity also helps to reduce drying shrinkage, promote internal stress dispersion and enhance anti-cracking performance.

[0010] Preferably, the mass ratio of the hydroxypropyl methylcellulose bulk, maleic anhydride and chlorosulfonic acid is 1:(1-1.4):2.

[0011] The modified cellulose ether water-retaining agent prepared according to the above mass ratio has good water-retaining properties and can synergize with polyacrylate to effectively improve the water-retaining properties, fluidity and anti-cracking properties of the mortar.

[0012] Preferably, the modified cellulose ether water retaining agent is prepared by the following steps: Dispersing hydroxypropyl methylcellulose in glacial acetic acid, stirring to obtain a hydroxypropyl methylcellulose solution, adding maleic anhydride to the hydroxypropyl methylcellulose solution, heating and stirring to react, adding anhydrous ethanol to precipitate after cooling, filtering, washing with anhydrous ethanol, and drying to obtain a preliminary modified product; The preliminary modified product prepared above is dispersed in dichloromethane and stirred until fully dissolved to obtain a preliminary product solution. Chlorosulfonic acid is added to the preliminary product solution under ice bath conditions and stirred to react. The solution after the reaction is neutralized with a sodium hydroxide aqueous solution, filtered, washed with water, and dried to obtain a modified cellulose ether water-retaining agent.

[0013] The modified cellulose ether water-retaining agent prepared according to the above steps has good water-retaining performance and can effectively improve the fluidity and anti-cracking performance of the mortar.

[0014] Preferably, the raw materials for preparing the polycarboxylate water-reducing agent include acrylic acid, N-[4-(sulfonamide)phenyl]acrylamide and methyl allyl polyoxyethylene ether.

[0015] The carboxyl group of acrylic acid can enhance the hydrophilicity of the water reducer and its adsorption to gypsum particles; the functional groups such as the sulfonamide group in N-[4-(sulfonamide)phenyl]acrylamide help to improve the dispersibility of the water reducer, so that the gypsum particles are evenly dispersed in the system, reducing particle agglomeration, thereby effectively reducing the friction between particles and improving the fluidity of the mortar; methyl allyl polyoxyethylene ether provides a good steric hindrance effect for the water reducer, which can further stabilize the dispersion state of the particles. This dispersing and stabilizing effect is conducive to maintaining the uniformity of the mortar system, reducing the water migration channel, and indirectly improving the water retention rate; at the same time, the evenly dispersed particles can be arranged and reacted more orderly during the hydration process, making the hardened mortar structure denser, reducing internal defects and stress concentration, and improving the anti-cracking performance.

[0016] Preferably, the raw materials for preparing the polycarboxylate water-reducing agent further include itaconic acid and dimethyldiallylammonium chloride.

[0017] Itaconic acid contains a long carbon chain and unsaturated double bonds in its molecular structure, which can provide a greater steric hindrance effect, thereby improving the adsorption stability and water retention capacity of the polycarboxylic acid water-reducing agent molecules on gypsum particles, better dispersing the particles, reducing the friction between particles during the flow of the mortar, and improving fluidity; dimethyldiallylammonium chloride carries a positive charge and can interact with the negatively charged surface of gypsum particles, enhancing the adsorption and dispersion effect of the water-reducing agent on the particles, making the mortar system more stable, thereby improving the water retention rate; the improvement of the dispersion and adsorption effects of the two can make the hydration reaction more complete and uniform, reduce internal weak points caused by particle agglomeration or uneven distribution, and good water retention can reduce drying shrinkage, thereby effectively enhancing the mortar's anti-cracking performance.

[0018] Preferably, the wollastonite powder is modified to obtain modified wollastonite powder, and the raw materials for preparing the modified wollastonite powder include wollastonite powder body, stearic acid and aluminate.

[0019] Stearic acid can react with the hydroxyl groups on the surface of wollastonite powder, changing the wollastonite powder from hydrophilic to hydrophobic, reducing its adsorption of water, thereby optimizing the moisture distribution in the mortar system and improving the water retention rate; at the same time, this modification changes the surface properties of the wollastonite powder, making it easier to disperse in the mortar, reducing the friction between particles and improving fluidity; aluminum hydroxide and other products generated by the hydrolysis of aluminate during the reaction are coated on the surface of the wollastonite powder, enhancing its bonding with the mortar matrix. This good bonding force, combined with the improved dispersibility brought about by stearic acid modification, enables the mortar to more effectively resist shrinkage stress during the hardening process, reduce the generation of cracks, and improve anti-cracking performance.

[0020] Preferably, the retarder comprises citric acid.

[0021] Citric acid can be adsorbed on the surface of hemihydrate gypsum particles. The carboxyl and hydroxyl groups in its molecules form complexes with calcium ions, which hinder the dissolution and hydration of hemihydrate gypsum, thereby prolonging the setting time, which is beneficial to improving the water retention rate, making the hydration reaction slower and more uniform, and reducing the phenomenon of excessive water consumption and uneven internal structure caused by too rapid hydration; the retarding effect of citric acid can maintain the fluidity of the mortar, allowing the particles to have more sufficient time to move and disperse in the water, preventing the fluidity from being reduced due to premature setting. Its regulation of hydration also helps to reduce the stress concentration caused by excessive local hydration, promote the formation of a uniform and dense structure, and thus enhance the mortar's resistance to cracking.

[0022] Preferably, the reinforcing fibers include polypropylene fibers and polyvinyl alcohol fibers.

[0023] Polypropylene fibers and polyvinyl alcohol fibers work synergistically to form a three-dimensional randomly distributed support system in the mortar, reinforcing the network structure, which can effectively inhibit shrinkage cracks caused by water loss, temperature changes and other factors in the plastic stage of the mortar; the reinforcing effect of the reinforcing fibers on the three-dimensional network can reduce the moisture migration channel, help maintain moisture inside the mortar, thereby improving the water retention rate, improving the stability of the mortar during the flow process, and reducing segregation; polypropylene fibers and polyvinyl alcohol fibers can bear and disperse tensile stress, prevent the expansion of cracks and the generation of new cracks, and improve the mortar's anti-cracking performance.

[0024] In a second aspect, the present application provides a method for preparing a high water retention gypsum self-leveling mortar, which adopts the following technical scheme: A method for preparing a high water retention gypsum self-leveling mortar comprises the following steps: The composite water retaining agent is dispersed in water and stirred to obtain a water retaining agent solution; a polycarboxylic acid water reducer and a retarder are added to the water retaining agent solution and stirred to obtain a mixed solution; wollastonite powder and hemihydrate gypsum are added to the mixed solution and stirred to obtain a slurry; reinforcing fibers are added to the slurry and stirred to obtain a gypsum self-leveling mortar with a high water retention rate.

[0025] The gypsum self-leveling mortar prepared according to the above steps has a high water retention rate, can maintain good fluidity, and has good anti-cracking performance.

[0026] In summary, the present application includes at least one of the following beneficial technical effects: 1. Hydroxypropyl methylcellulose in the composite water retaining agent forms hydrogen bonds with water molecules through the hydroxyl groups on the molecular chain, and entangles with each other to form a three-dimensional network structure. Polyacrylic acid salt relies on a large number of hydrophilic groups such as carboxyl groups to absorb water molecules through electrostatic attraction and hydrogen bonds. The two are interwoven to form a stable water retention system, thereby greatly improving the water retention rate and improving the rheological properties; the three-dimensional network structure can appropriately increase the viscosity, make the mortar flow smoothly, and evenly distribute the particles to prevent segregation. Polyacrylic acid salt is adsorbed on the surface of gypsum particles to generate electrostatic repulsion, reducing the friction between particles. The combination of the two allows the mortar to flow more smoothly while maintaining a certain viscosity; polycarboxylic acid water reducer and retarder work synergistically with the composite water retaining agent to regulate the performance of the mortar, improve its water retention rate, fluidity and crack resistance; wollastonite powder can fill pores and reduce water loss channels, thereby improving water retention performance; reinforcing fibers can improve the stability of the three-dimensional network structure and reinforce defects, thereby improving crack resistance.

[0027] 2. Maleic anhydride can introduce more polar groups into the molecular chain of cellulose ether and enhance its adsorption capacity for water molecules; chlorosulfonic acid can further change its molecular structure, introduce sulfonic acid groups, increase its hydrophilicity and the number of sites for binding with water molecules, so that the modified cellulose ether water retaining agent can lock moisture more effectively in the mortar and further improve the water retention rate; its optimized molecular structure can better adjust the rheological properties of the mortar, improve the interaction between particles and enhance fluidity; stronger water retention capacity also helps to reduce drying shrinkage, promote internal stress dispersion and enhance anti-cracking performance.

[0028] 3. The carboxyl group of acrylic acid can enhance the hydrophilicity of the water reducer and its adsorption to gypsum particles; the sulfonamide group and other functional groups in N-[4-(sulfonamide)phenyl]acrylamide help to improve the dispersibility of the water reducer, making the gypsum particles evenly dispersed in the system, reducing particle agglomeration, thereby effectively reducing the friction between particles and improving the fluidity of the mortar; methyl allyl polyoxyethylene ether provides a good steric hindrance effect for the water reducer, which can further stabilize the dispersion state of the particles; the molecular structure of itaconic acid contains a long carbon chain and an unsaturated double bond, which can provide a greater steric hindrance effect, thereby enhancing the polycarboxylic acid The adsorption stability and water retention capacity of the water reducer molecules on the gypsum particles can better disperse the particles, reduce the friction between the particles during the flow of the mortar, and improve the fluidity; dimethyldiallyl ammonium chloride has a positive charge and can interact with the negatively charged surface of the gypsum particles, thereby enhancing the adsorption and dispersion effect of the water reducer on the particles, making the mortar system more stable, thereby improving the water retention rate; the improvement of the dispersion and adsorption effect can make the hydration reaction more complete and uniform, reduce the internal weak points caused by particle agglomeration or uneven distribution, and the good water retention performance reduces drying shrinkage, thereby effectively enhancing the mortar's anti-cracking performance. DETAILED DESCRIPTION

[0029] The present application discloses a high water retention gypsum self-leveling mortar and a preparation method thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Ingredients: Hydroxypropyl methylcellulose (CAS: 9004-65-3), maleic anhydride (CAS: 108-31-6), chlorosulfonic acid (CAS: 7790-94-5), methyl allyl polyoxyethylene ether HPEG-2400 (CAS: 27274-31-3), acrylic acid (CAS: 79-10-7), N-[4-(sulfonamide)phenyl]acrylamide (CAS: 2621-99-0), itaconic acid (CAS: 97-65-4), dimethyl dimethicone Allyl ammonium chloride (CAS No.: 7398-69-8) and wollastonite powder were purchased from Changxing Huaqi New Materials Co., Ltd. Stearic acid (CAS No.: 57-11-4), sodium aluminate (CAS No.: 1302-42-7), polypropylene fiber and polyvinyl alcohol fiber were purchased from Shandong Hongshuo New Materials Co., Ltd. The polyacrylate was sodium polyacrylate (CAS No.: 9003-04-7), the retarder was citric acid (CAS No.: 77-92-9), and the semi-hydrated gypsum was α-semi-hydrated gypsum with a purity of 95% and a fineness of 300 mesh.

[0030] Preparation Example 1 Preparation of modified cellulose ether water-retaining agent Disperse 2.5 kg of hydroxypropyl methylcellulose in 5 L of glacial acetic acid, stir at 300 rpm for 30 min to obtain a hydroxypropyl methylcellulose solution, add 2.5 kg of maleic anhydride to the hydroxypropyl methylcellulose solution, stir and react at 90 ° C at 300 rpm for 5 h, after cooling to below 30 ° C, add anhydrous ethanol for precipitation, filter and wash with anhydrous ethanol, and dry in an oven at 50 ° C to obtain a preliminary modified product.

[0031] The preliminary modified product prepared above was dispersed in 10L of dichloromethane and stirred at 400rpm until completely dissolved to obtain a preliminary product solution. 5kg of chlorosulfonic acid was added to the preliminary product solution under ice bath conditions within 3h. The reaction was stirred for 6h. The solution after the reaction was neutralized with 1mol / L sodium hydroxide aqueous solution, filtered, washed with deionized water, and dried at 60°C to obtain a modified cellulose ether water-retaining agent.

[0032] Preparation Example 2 Preparation Example 2 is based on Preparation Example 1. The only difference between Preparation Example 2 and Preparation Example 1 is that in Preparation Example 2, the amount of hydroxypropyl methylcellulose used is 2.27 kg, the amount of maleic anhydride used is 3.18 kg, and the amount of chlorosulfonic acid used is 4.55 kg.

[0033] Preparation Example 3 Preparation Example 3 is based on Preparation Example 1. The only difference between Preparation Example 3 and Preparation Example 1 is that in Preparation Example 3, the amount of hydroxypropyl methylcellulose used is 2.38 kg, the amount of maleic anhydride used is 2.86 g, and the amount of chlorosulfonic acid used is 4.76 kg.

[0034] Preparation Example 4 Preparation Example 4 is based on Preparation Example 1. The only difference between Preparation Example 4 and Preparation Example 1 is that in Preparation Example 4, the amount of hydroxypropyl methylcellulose used is 2.63 kg, the amount of maleic anhydride used is 2.11 kg, and the amount of chlorosulfonic acid used is 5.26 kg.

[0035] Preparation Example 5 Preparation Example 5 is based on Preparation Example 1. The only difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, the amount of hydroxypropyl methylcellulose used is 2.17 kg, the amount of maleic anhydride used is 3.48 kg, and the amount of chlorosulfonic acid used is 4.35 kg.

[0036] Preparation Example 6 Preparation of polycarboxylate water reducer 0.2 kg of methyl allyl polyoxyethylene ether is dispersed in 1 L of deionized water, and stirred at 300 rpm at 50 ° C until fully dissolved to obtain a methyl allyl polyoxyethylene ether solution; 0.75 kg of acrylic acid and 0.05 kg of N-[4-(sulfonamide)phenyl] acrylamide are dispersed in 2 L of deionized water to obtain a monomer solution, and the monomer solution is added to the methyl allyl polyoxyethylene ether solution, and the addition is completed within 2 hours. While adding the monomer solution, 200 mL of a potassium persulfate solution with a mass concentration of 10% is added to the methyl allyl polyoxyethylene ether solution, and the addition is completed within 3 hours. After the addition of the monomer solution is completed, 180 mL of a 5% thioacetic acid aqueous solution is added, and the addition is completed within 1 hour. The reaction is kept at 60 ° C for 1 hour, and the temperature is reduced to 30 ° C to obtain a product solution. 1 mol / L of sodium hydroxide aqueous solution is added to the product solution for neutralization so that the pH is 7, and the polycarboxylic acid water reducer is obtained after concentration and drying.

[0037] Preparation Example 7 Preparation Example 7 is based on Preparation Example 6. The only difference between Preparation Example 7 and Preparation Example 6 is that the raw materials for preparing the polycarboxylate water-reducing agent in Preparation Example 7 also include itaconic acid and dimethyldiallylammonium chloride.

[0038] 0.2 kg of methyl allyl polyoxyethylene ether was dispersed in 1 L of deionized water, and stirred at 300 rpm at 50 ° C until fully dissolved to obtain a methyl allyl polyoxyethylene ether solution; 0.6 kg of acrylic acid, 0.05 kg of N-[4-(sulfonamide)phenyl] acrylamide, 0.1 kg of itaconic acid and 0.05 kg of dimethyl diallyl ammonium chloride were dispersed in 2 L of deionized water to obtain a monomer solution, and the monomer solution was added to the methyl allyl polyoxyethylene ether solution within 2.5 hours. While adding the monomer solution, add 200 mL of a 10% potassium persulfate solution to the methyl allyl polyoxyethylene ether solution, and complete the addition within 4 hours. After the monomer solution is added, add 150 mL of a 5% thioacetic acid aqueous solution, and complete the addition within 1 hour. Keep the reaction at 60° C. for 1 hour, cool to 30° C. to obtain a product solution, add 1 mol / L sodium hydroxide aqueous solution to the product solution for neutralization to a pH of 7, and concentrate and dry to obtain a polycarboxylic acid water reducer.

[0039] Preparation Example 8 Preparation of modified wollastonite powder The wollastonite powder was washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 100°C to obtain dry wollastonite powder; 18.52 kg of dry wollastonite powder and 0.93 kg of stearic acid were dispersed in 30 L of anhydrous ethanol, heated to 80°C and stirred at 300 rpm for reaction for 2 hours, and the solvent was removed by rotary evaporation to obtain preliminary modified wollastonite powder; 0.55 kg of sodium aluminate was dissolved in 1 L of deionized water to obtain a sodium aluminate solution, and the sodium aluminate solution was added to the preliminary modified wollastonite powder, and the pH was controlled to 10 with a 1 mol / L sodium hydroxide aqueous solution, and the temperature was raised to 80°C for reaction for 2 hours, and then raised to 120°C for reaction for 1 hour, and then cooled to 30°C, filtered to obtain a modified solid product, and the modified solid product was washed with deionized water, and dried at 80°C to obtain modified wollastonite powder.

[0040] Example 1 4 kg of composite water-retaining agent was dispersed in 15 kg of water, wherein the mass ratio of hydroxypropyl methylcellulose to polyacrylate in the composite water-retaining agent was 2:1, and the mixture was stirred at 1000 rpm for 10 min to obtain a water-retaining agent solution; 0.1 kg of the polycarboxylic acid water-reducing agent prepared in Preparation Example 6 and 0.008 kg of retarder were added to the water-retaining agent solution, and the mixture was stirred at 800 rpm for 5 min to obtain a mixed solution; 5 kg of wollastonite powder and 60 kg of hemihydrate gypsum were added to the mixed solution, and the mixture was stirred at 300 rpm for 15 min to obtain a slurry; 1 kg of reinforcing fiber was added to the slurry, wherein the mass ratio of polypropylene fiber to polyvinyl alcohol fiber in the reinforcing fiber was 1:1, and the mixture was stirred at 500 rpm for 30 min to obtain a gypsum self-leveling mortar with a high water retention rate.

[0041] Example 2 8 kg of composite water-retaining agent was dispersed into 25 kg of water, wherein the mass ratio of hydroxypropyl methylcellulose to polyacrylate in the composite water-retaining agent was 2:1, and the mixture was stirred at 1000 rpm for 10 min to obtain a water-retaining agent solution; 0.5 kg of the polycarboxylic acid water-reducing agent prepared in Preparation Example 6 and 0.012 kg of retarder were added to the water-retaining agent solution, and the mixture was stirred at 800 rpm for 5 min to obtain a mixed solution; 15 kg of wollastonite powder and 80 kg of hemihydrate gypsum were added to the mixed solution, and the mixture was stirred at 300 rpm for 15 min to obtain a slurry; 3 kg of reinforcing fiber was added to the slurry, wherein the mass ratio of polypropylene fiber to polyvinyl alcohol fiber in the reinforcing fiber was 1:1, and the mixture was stirred at 500 rpm for 30 min to obtain a gypsum self-leveling mortar with a high water retention rate.

[0042] Example 3 6 kg of composite water-retaining agent was dispersed into 20 kg of water, wherein the mass ratio of hydroxypropyl methylcellulose to polyacrylate in the composite water-retaining agent was 2:1, and the mixture was stirred at 1000 rpm for 10 min to obtain a water-retaining agent solution; 0.3 kg of the polycarboxylic acid water-reducing agent prepared in Preparation Example 6 and 0.001 kg of retarder were added to the water-retaining agent solution, and the mixture was stirred at 800 rpm for 5 min to obtain a mixed solution; 10 kg of wollastonite powder and 70 kg of hemihydrate gypsum were added to the mixed solution, and the mixture was stirred at 300 rpm for 15 min to obtain a slurry; 2 kg of reinforcing fiber was added to the slurry, wherein the mass ratio of polypropylene fiber to polyvinyl alcohol fiber in the reinforcing fiber was 1:1, and the mixture was stirred at 500 rpm for 30 min to obtain a gypsum self-leveling mortar with a high water retention rate.

[0043] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, hydroxypropyl methylcellulose is replaced by the modified cellulose ether water-retaining agent prepared in Preparation Example 1.

[0044] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, hydroxypropyl methylcellulose is replaced by the modified cellulose ether water-retaining agent prepared in Preparation Example 2.

[0045] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, hydroxypropyl methylcellulose is replaced by the modified cellulose ether water-retaining agent prepared in Preparation Example 3.

[0046] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, hydroxypropyl methylcellulose is replaced by the modified cellulose ether water-retaining agent prepared in Preparation Example 4.

[0047] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, hydroxypropyl methylcellulose is replaced by the modified cellulose ether water-retaining agent prepared in Preparation Example 5.

[0048] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, the polycarboxylate water-reducing agent prepared in Preparation Example 6 is replaced by the polycarboxylate water-reducing agent prepared in Preparation Example 7.

[0049] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, the wollastonite powder is replaced by the modified wollastonite powder prepared in Preparation Example 8.

[0050] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that in Example 11, no polyvinyl alcohol fiber is added to the reinforcing fiber.

[0051] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that the composite water-retaining agent in Comparative Example 1 is replaced by hydroxypropyl methylcellulose.

[0052] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that wollastonite powder is not added in Comparative Example 2.

[0053] Comparative Example 3 Comparative Example 3 is based on Example 3, and the only difference between Comparative Example 3 and Example 3 is that no reinforcing fiber is added in Comparative Example 3.

[0054] Comparative Example 4 Comparative Example 4 is based on Example 3, and the only difference between Comparative Example 4 and Example 3 is that no retarder is added in Comparative Example 4.

[0055] Performance testing (1) Fluidity test: The standard "JC / T1023-2007 Gypsum-based Self-leveling Mortar" was selected. The flow diameter of the test sample in two vertical directions was measured and the average value was taken. The test was carried out in the initial state and after standing for 30 minutes. The results are recorded in Table 1.

[0056] (2) Anti-cracking performance test: The "JGJ / T 70-2009 Standard for Test Methods for Basic Performance of Building Mortar" was selected as the standard. The sample was poured into a shrinkage mold and demolded after 24 hours. The initial length of the specimen was tested and recorded. After the test, the specimen was dried in an electric hot air drying oven at 40°C to constant weight. The length of the specimen after drying was tested and the shrinkage rate was calculated. Each specimen was tested three times and the average value was taken after measurement. The results are recorded in Table 1.

[0057] Table 1 Test results of fluidity and anti-cracking performance It can be seen from Table 1 that the initial fluidity of Examples 1-3 is 150-152 mm, the 30 min fluidity is 143-145 mm, and the shrinkage is less than 0.034%. It can be seen that the gypsum self-leveling mortar prepared in the present application has good fluidity and anti-cracking performance.

[0058] As can be seen from Table 1, the only difference between Example 4-8 and Example 3 is that in Example 4-8, hydroxypropyl methylcellulose is replaced by a modified cellulose ether water-retaining agent, and the synthetic component ratio of the modified cellulose ether water-retaining agent in Example 4-6 is within a limited range, has good water-retaining performance, can make the mortar maintain good fluidity, and improve its anti-cracking performance; compared with Example 4-6, Examples 7 and 8 destroy the limited ratio, affect the cross-linking structure and stability of the water-retaining agent, reduce the water retention rate, and further affect the fluidity and anti-cracking performance.

[0059] As can be seen from Table 1, the only difference between Example 9 and Example 3 is that in Example 9, the polycarboxylate water-reducer prepared in Preparation Example 6 is replaced by the polycarboxylate water-reducer prepared in Preparation Example 7. Compared with Example 3, Example 9 has improved anti-cracking performance; this is because itaconic acid molecules and quaternary ammonium salt molecules are introduced into the polycarboxylate water-reducer molecules, which can improve the adsorption stability and water retention capacity, so that the mortar has a good water retention state, reduces internal weaknesses and defects, and thus improves the anti-cracking performance.

[0060] It can be seen from Table 1 that the only difference between Example 10 and Example 3 is that in Example 10, the wollastonite powder is replaced by the modified wollastonite powder prepared in Preparation Example 8. Compared with Example 3, the fluidity and crack resistance of Example 10 are improved; this is because the wollastonite powder is modified, and the modified wollastonite powder has good dispersibility, can effectively improve the water retention rate, and reduce the friction between particles, so that the mortar can more effectively resist shrinkage stress and improve the anti-cracking performance.

[0061] It can be seen from Table 1 that the only difference between Example 11 and Example 3 is that no polyvinyl alcohol fiber is added to the reinforcing fiber in Example 11, and compared with Example 3, the anti-cracking performance of Example 11 is reduced; this is because there is a lack of synergistic effect of polyvinyl alcohol fiber and polypropylene fiber, the reinforcement effect is reduced, which in turn affects the stability of the mortar, thereby reducing the anti-cracking performance.

[0062] As can be seen from Table 1, the only difference between Comparative Example 1 and Example 3 is that the composite water-retaining agent is replaced with hydroxypropyl methylcellulose in Comparative Example 1. Compared with Example 3, the fluidity and anti-cracking performance of Comparative Example 1 are reduced. This is because the lack of polyacrylate reduces the dispersibility of the mortar, deteriorates the fluidity, reduces the water retention capacity, and makes the system more susceptible to shrinkage, thereby deteriorating the anti-cracking performance.

[0063] It can be seen from Table 1 that the only difference between Comparative Examples 2-4 and Example 3 is that no wollastonite powder is added in Comparative Example 2, no reinforcing fiber is added in Comparative Example 3, and no retarder is added in Comparative Example 4. Compared with Example 3, the performance of Comparative Examples 2-4 is reduced; this is because if no wollastonite powder is added, the water retention performance is reduced, thereby the anti-cracking performance deteriorates; if no reinforcing fiber is added, the three-dimensional network structure lacks reinforcement, the stability is reduced, and the anti-cracking performance deteriorates; if no retarder is added, the fluidity of the mortar decreases rapidly, and too fast hydration is prone to stress concentration, thereby affecting the anti-cracking performance.

[0064] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A high water retention gypsum self-leveling mortar, characterized in that: The composition includes the following components in parts by weight: 60-80 parts of hemihydrate gypsum 4-8 parts of composite water retaining agent Polycarboxylate water reducer 0.1-0.5 parts Wollastonite powder 5-15 parts Retarder 0.008-0.012 parts Reinforced fiber 1-3 parts 15-25 parts water; The composite water-retaining agent comprises hydroxypropyl methylcellulose and polyacrylate.

2. The high water retention gypsum self-leveling mortar according to claim 1, characterized in that: The hydroxypropyl methylcellulose is subjected to modification treatment to obtain a modified cellulose ether water retaining agent, and the raw materials for preparing the modified cellulose ether water retaining agent include hydroxypropyl methylcellulose body, maleic anhydride and chlorosulfonic acid.

3. The high water retention gypsum self-leveling mortar according to claim 2, characterized in that: The mass ratio of the hydroxypropyl methylcellulose bulk, maleic anhydride and chlorosulfonic acid is 1:(1-1.4):

2.

4. The high water retention gypsum self-leveling mortar according to claim 3, characterized in that: The modified cellulose ether water retaining agent is prepared by the following steps: Dispersing hydroxypropyl methylcellulose in glacial acetic acid, stirring to obtain a hydroxypropyl methylcellulose solution, adding maleic anhydride to the hydroxypropyl methylcellulose solution, heating and stirring to react, adding anhydrous ethanol to precipitate after cooling, filtering, washing with anhydrous ethanol, and drying to obtain a preliminary modified product; The preliminary modified product prepared above is dispersed in dichloromethane and stirred until fully dissolved to obtain a preliminary product solution. Chlorosulfonic acid is added to the preliminary product solution under ice bath conditions and stirred to react. The solution after the reaction is neutralized with a sodium hydroxide aqueous solution, filtered, washed with water, and dried to obtain a modified cellulose ether water-retaining agent.

5. The high water retention gypsum self-leveling mortar according to claim 1, characterized in that: The raw materials for preparing the polycarboxylic acid water-reducing agent include acrylic acid, N-[4-(sulfonamide)phenyl]acrylamide and methyl allyl polyoxyethylene ether.

6. The high water retention gypsum self-leveling mortar according to claim 5, characterized in that: The raw materials for preparing the polycarboxylate water-reducing agent also include itaconic acid and dimethyldiallylammonium chloride.

7. The high water retention gypsum self-leveling mortar according to claim 1, characterized in that: The wollastonite powder is modified to obtain modified wollastonite powder. The raw materials for preparing the modified wollastonite powder include wollastonite powder body, stearic acid and aluminate.

8. The high water retention gypsum self-leveling mortar according to claim 1, characterized in that: The retarder includes citric acid.

9. The high water retention gypsum self-leveling mortar according to claim 1, characterized in that: The reinforcing fibers include polypropylene fibers and polyvinyl alcohol fibers.

10. A method for preparing a high water retention gypsum self-leveling mortar as claimed in any one of claims 1 to 9, characterized in that: The steps include: Dispersing the composite water retaining agent in water and stirring to obtain a water retaining agent solution; adding the polycarboxylic acid water reducer and the retarder to the water retaining agent solution and stirring to obtain a mixed solution; adding wollastonite powder and hemihydrate gypsum to the mixed solution and stirring to obtain a slurry; Reinforced fibers are added to the slurry and stirred to obtain a gypsum self-leveling mortar with high water retention rate.